Clays and the minerals processing value chain (MPVC) - Gräfe, M.; McFarlane, A.; Klauber, Craig (Cambridge University Press, 2017)
© Commonwealth Scientific and Industrial Research Organisation (CSIRO) 2017. Introduction Clays represent the raw material for mankind's first transformed product, namely pottery (e.g. Schroeder and Erickson, 2014). While remaining important as a raw material on their own, they are increasingly seen as a major problem in the mining, extraction and value-adding processes for a wide range of commodity raw materials. Clays can impact negatively on virtually every unit process within the mining and minerals processing sector. The extent of this impact is shown schematically in Fig. 1.1. These impacts can vary from trivial problems such as cleaning mining machinery through to serious mining and materials handling safety issues. The common issues can be summarized as either relating to materials handling (rheological consequences and ‘stickiness’), rheological or chemical interference in a beneficiation (or upgrading) process and impacting upon general solid–liquid separation operations. The latter in particular is not only germane to many parts of the mineral processing operation (e.g. S/L in Fig. 1.1), but almost invariably is the last operation prior to tailings disposal. Moreover, these issues continue to operate, often with negative consequences, for tailings areas pre- and post-closure. Presence of clay(s) and clay behaviour can thus have long-term environmental implications that go well beyond the lifetime of the mining and refining operations. Mining and mineral processing are very energy intensive – in comparison to the agricultural sector, the energy intensity (per dollar added to the economy) is typically 2–3 times greater (Rábago et al., 2001). Whether the commodity is a high-value item such as gold (usually found in parts per million (ppm) concentrations) or an almost pure but low-value bulk commodity such as iron ore, typical operations handle many millions of tonnes of ore material each year. Every time material is handled and for every change in physical state (size range, temperature, pressure, etc.) or chemical environment (pH, Eh, ionic strength, solution composition, etc.) there is a cost penalty in terms of energy, time, raw material inputs and often additional labour and capital expenditure, and the recurring cost thereby entailed. When present in the ore-body, clays cannot be easily removed in the mining phase because of their intimate association with other gangue minerals. Minimizing their impact along the value chain is critical to reducing costs and improving overall efficiencies, hence an understanding of clay behaviour is fundamental to achieving greater overall cost and handling efficiencies.